Seasonal variation and role of meteorological conditions in reported chicken pox cases in a residential hostel of Ramgarh - Gupta, Vivek; Kumar, Surinder; Mahajan, Saurabh (International Journal Of Community Medicine And Public Health, 2021)
Background: Chicken pox is an acute, common, and highly contagious disease caused by the varicella zoster virus (VZV). Chicken pox is predominantly a childhood disease characterized by pruritic vesicular exanthema with systemic symptoms such as fever, loss of appetite, and malaise. Primary infection tends to occur at a younger age and is usually benign in immunocompetent children but can be life-threatening in adults and immunocompromised individuals, with an attack rate approaching >85% after exposure. This study attempts to evaluate the trend of chickenpox cases in a residential hostel in Ramgarh. Methods: This was a record based descriptive study done using reported Chicken Pox cases in the OPDs during the period from January 2015 to December 2018. Monthly average for meteorological data (Min and Max temperature, Precipitation and Humidity) for Ramgarh was recorded for the study period. Seasonality and trend was identified for chicken pox cases during this period by plotting the monthly number of clinically diagnosed cases over time period to identify any repeated pattern. Poisson’s distribution was used to estimate association between meteorological variables and incidence of chickenpox cases. Results: Analysis revealed strong correlations (r=0.7553, p<0.0001) between humidity and precipitation. There was a significant correlation between Incidence of varicella and meteorological factors under study (all p<0.05). Conclusions: The findings of this study will aid in forecasting epidemics and in preparing for the impact of climate change on the varicella epidemiology through the implementation of public health preventive measures such as promoting good hygiene practices, temporary closure of educational institutions, active vaccination and campaigns that include press releases and media events to encourage preventive activities.